Prevalence and risk factors of Strongyloides stercoralis in Takeo Province, Cambodia - Khieu, Virak (BioMed Central, 2014)
BACKGROUND: The threadworm Strongyloides stercoralis, the most neglected helminth, affects an estimated 30-100 million people worldwide. Information on S. stercoralis infection is scarce in tropical and sub-tropical resource poor countries, including Cambodia. We determined S. stercoralis infection prevalence and risk factors for infection in the general population in Southern Cambodia. METHODS: A cross-sectional study was carried out between January and April 2011 among 2,861 participants living in 60 villages of Takeo province, using Koga-agar plate culture, the Baermann technique and the Kato-Katz technique on a single stool sample. RESULTS: Eight intestinal helminth species were diagnosed. Hookworm (31.4%) and S. stercoralis (21.0%) occurred most frequently. Prevalence of S. stercoralis infection increased with age. In all age groups a higher prevalence was found among males than among females (OR: 1.7; 95% CI: 1.4 – 2.0; P < 0.001). Participants who had a latrine at home were significantly less frequently infected with S. stercoralis than those who did not (OR: 0.7; 95% CI: 0.4 – 0.8; P = 0.003). Muscle pain (OR: 1.3; 95% CI: 1.0 – 1.6; P = 0.028) and urticaria (OR: 1.4; 95% CI: 1.1 – 1.8; P = 0.001) were significantly associated with S. stercoralis infection. CONCLUSIONS: S. stercoralis is highly prevalent among the general Cambodian population and should no longer be neglected. Access to adequate diagnosis and treatment is urgently needed.